Main directions and perspectives of development of ecological tourism in Navoi region. - Islomova R.A; Idrisova Sh (Proceedings of The ICECRS, 2020)
This paper makes analyses of the main directions and perspectives of development of ecological tourism in Navoi region. On this case, research has been pinpointed from various points to make better development prospectives. Outcomes and shortcomings of the tourism perspectives in ecological tourism in Navoiy region were stated with highlights. In conclusion, research has been finizalized with major recommendations for the future research points.